Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/adom.201801350
|View full text |Cite
|
Sign up to set email alerts
|

Optical Anapoles: Concepts and Applications

Abstract: Interference of electromagnetic modes supported by subwavelength photonic structures is one of the key concepts that underpins the nanoscale control of light in metaoptics. It drives the whole realm of all‐dielectric Mie‐resonant nanophotonics with many applications for low‐loss nanoscale optical antennas, metasurfaces, and metadevices. Specifically, interference of the electric and toroidal dipole moments results in a very peculiar, low‐radiating optical state associated with the concept of optical anapole. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
177
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(186 citation statements)
references
References 81 publications
2
177
0
Order By: Relevance
“…While this nonradiating polarization distribution can indeed be interpreted as arising from the cancellation of quasi-static Cartesian dipolar and toroidal contributions, as discussed in Ref. [9,12], we would like to stress that it is not different from any other scattering zero of the dipolar Mie coefficient, as observed in Fig. 1(c) along the wavelength axis, other than the fact that, given the long wavelength, all other multipolar scattering contributions happen to be small.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…While this nonradiating polarization distribution can indeed be interpreted as arising from the cancellation of quasi-static Cartesian dipolar and toroidal contributions, as discussed in Ref. [9,12], we would like to stress that it is not different from any other scattering zero of the dipolar Mie coefficient, as observed in Fig. 1(c) along the wavelength axis, other than the fact that, given the long wavelength, all other multipolar scattering contributions happen to be small.…”
mentioning
confidence: 59%
“…Introduction -The ability to tailor optical scattering in anomalous and extreme ways, beyond what is achievable with conventional optical materials and structures, has been for several years one of the fundamental goals of optical metamaterials and nanophotonic systems [1]. Rapid progress in these fields has enabled the realization of a plethora of anomalous scattering effects, including invisibility [2][3][4][5][6], ultra-sharp Fano scattering resonances [7,8], non-scattering anapole scatterers [9][10][11][12][13][14][15][16], and bound states in the continuum or embedded eigenstates [17][18][19][20][21][22]. Scattering engineering plays a fundamental role in modern photonics research, for applications spanning from wavefront manipulation [23] and optical signal processing [24,25], to energy harvesting [26] and sensing [27], to mention just a few.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For more details of the multipole analysis, refer to Supplementary Information section I. Such highorder modes supported by the metamaterial [28][29][30] enable strong light localization and confinement, which may be suitable for applications in nonlinear and laser optics, 31,32 Overall, the TI chalcogenide crystal family is an exceptionally versatile material platform for infrared applications based on high-index, low-loss dielectric metamaterial architectures, including ultrathin flat optical elements 33 , sub-diffraction light confinement and waveguiding 34 , and nonlinear optics 35 . Low-loss mid-IR metamaterials are also highly sought for enhanced sensing of molecular fingerprints based on strong light confinement.…”
Section: Figure 2amentioning
confidence: 99%
“…Typical shapes of halide-perovskite meta-atoms are spheres, cubes, and cylinders, as shown in Figs. 3a-c. Optical response of dielectric nanoparticles of various shapes has been studied intensively during last few years [59][60][61][62] , and it was revealed that the scattering properties of dielectric nanoparticles depend strongly on the geometric parameters and the value of the material refractive index. According to Fig.…”
Section: A Optical Resonances In Dielectric Meta-opticsmentioning
confidence: 99%